Evaluation of the Sustainability of Waste Reduction Training for the Community: A Case Study of the Rutela Group as a Partner of Pertamina Patra Niaga Fuel Terminal Tegal - Naura Alika Reswara; Muchlisah Harliani; Emi Ulfianah (Global Writing Academica Researching and Publishing, 2025)
Waste remains an unresolved environmental issue in Indonesia that has yet to be resolved. One of the contributing factors is the lack of public awareness regarding waste reduction efforts. Although various initiatives have been undertaken to raise awareness through training and knowledge-sharing activities, the long-term impact of such training programs on waste reduction remains underreported. This study aims to examine the sustainability impact of training activities conducted by the Rutela Group and how these activities contribute to waste reduction efforts in Tegal City. A quantitative method supplemented by qualitative data was employed, with the research conducted in Randugunting Subdistrict, Tegal City. The study identified two forms of training sustainability: (1) the implementation of follow-up training and (2) the continuation of collaboration between training participants and the Rutela Group. The training activities showed considerable potential in encouraging participants to engage in waste reduction practices. Several key factors were identified to support post-training waste reduction activities, including the involvement of senior high school students as participants, the proactive initiation of further collaboration by the training organizers, and the emphasis on short-term economic benefits that could be gained by participants through waste reduction practices after the training.